(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the relevant literature on the experience of using a home chemical experiment abroad and in our republic, on the role of a home experiment in the development of experimental skills along with laboratory work, practical exercises and a demonstration experiment, as well as the results of a study on this issue.